Adhesive layer for flexible image display device, laminate for flexible image display device, and flexible image display device

By using the adhesive layer of (meth)acrylic polymer and the protective film of transparent resin material in an organic EL display device, combined with the polarization film, the problem of hindered bending in the prior art is solved, and repeated bending is achieved A flexible image display device that does not peel and bending resistance.

CN119119899APending Publication Date: 2024-12-13NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411187812.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-08-15
Filing Date
2017-08-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When the conventional organic EL display device is laminated with a polarizing film, a protective film and a phase difference film, the bending properties are hindered, resulting in the flexible image display device that is repeatedly bending without peeling or breaking.

Method used

The adhesive layer of the flexible image display device is formed by a binder composition containing (meth)acrylic polymer, with a weight average molecular weight of 1 million to 2.5 million, a glass transition temperature of 0°C or less, and is stacked on the A protective film and polarizing film of transparent resin material are used in the body. The preferred thickness of the adhesive layer is 5 to 150 μm, the energy storage modulus is 1.0 MPa or less at 25°C, and the adhesive force is 5 to 40N/25mm.

Benefits of technology

A flexible image display device with no peeling off for repeated bending, excellent bending resistance and adhesion is realized, ensuring the flexibility and service life of the laminated body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119899A_ABST
    Figure CN119119899A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: an adhesive layer for a flexible image display device, which does not peel off or break even when bent repeatedly and has excellent bending resistance and adhesion; and a laminate for a flexible image display device, which contains the adhesive layer for a flexible image display device. And a flexible image display device in which the laminate for flexible image display devices is disposed. The adhesive layer for a flexible image display device according to the present invention is formed from an adhesive composition containing a (meth) acrylic polymer, the weight-average molecular weight (Mw) of the (meth) acrylic polymer being 1,000,000-25,000,000, and the glass transition temperature (Tg) of the adhesive layer being 0 DEG C or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application filed on August 2, 2017, with application number 201780050094.5 and invention name “Adhesive layer for flexible image display device, laminate for flexible image display device, and flexible image display device”. Technical Field

[0002] The present invention relates to a pressure-sensitive adhesive layer for a flexible image display device, a laminate for a flexible image display device, and a flexible image display device having the laminate for a flexible image display device. Background Art

[0003] As an example of an image display device using a conventional organic EL, Figure 1 An image display device of the structure shown. An optical laminate 20 is provided on the visible side of an organic EL display panel 10, and a touch panel 30 is provided on the visible side of the optical laminate 20. The optical laminate 20 includes a polarizing film 1 and a phase difference film 3 with protective films 2-1 and 2-2 bonded to both sides, and the polarizing film 1 is provided on the visible side of the phase difference film 3. In addition, the touch panel 30 has a structure in which transparent conductive films 4-1 and 4-2 are arranged with a spacer 7 interposed therebetween, and the transparent conductive films 4-1 and 4-2 have a structure in which base films 5-1 and 5-2 and transparent conductive layers 6-1 and 6-2 are laminated (for example, refer to Patent Document 1).

[0004] For such image display devices, a bendable flexible image display device is required, and studies have been conducted on adhesive layers used for such devices.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-157745 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The existing organic EL display device shown in Patent Document 1 is not designed with bending in mind. If a plastic film is used in the organic EL display panel substrate, the organic EL display panel can be given bending properties. In addition, when a plastic film is used in a touch panel and introduced into the organic EL display panel, the organic EL display panel can also be given bending properties. However, the optical laminated body stacked in the organic EL display panel with the existing polarizing film, its protective film, and phase difference film will cause the problem of hindering the bending properties of the organic EL display device.

[0010] Therefore, the object of the present invention is to provide an adhesive layer for a flexible image display device that will not peel off or break even after repeated bending and has excellent bending resistance and adhesion, a laminate for a flexible image display device comprising the above-mentioned adhesive layer for a flexible image display device, and a flexible image display device equipped with the above-mentioned laminate for a flexible image display device.

[0011] Solutions to the problem

[0012] The adhesive layer for a flexible image display device of the present invention is formed from an adhesive composition containing a (meth)acrylic polymer, wherein the weight average molecular weight (Mw) of the (meth)acrylic polymer is 1 million to 2.5 million, and the glass transition temperature (Tg) of the adhesive layer is below 0°C.

[0013] The pressure-sensitive adhesive layer for a flexible image display device of the present invention preferably has a storage modulus G′ at 25° C. of 1.0 MPa or less.

[0014] The adhesive force of the pressure-sensitive adhesive layer for a flexible image display device of the present invention to the polarizing plate is preferably 5 to 40 N / 25 mm.

[0015] It is preferred that the laminate for a flexible image display device of the present invention comprises the pressure-sensitive adhesive layer for a flexible image display device, a protective film of a transparent resin material, and a polarizing film in this order.

[0016] Preferably, the flexible image display device of the present invention includes the laminate for a flexible image display device and an organic EL display panel, wherein the laminate for a flexible image display device is arranged on a visible side of the organic EL display panel.

[0017] Effects of the Invention

[0018] The adhesive layer for a flexible image display device of the present invention can obtain a laminate for a flexible image display device that does not peel off even after repeated bending and has excellent bending resistance and adhesion. Furthermore, it can obtain a flexible image display device equipped with the laminate for a flexible image display device, which is useful.

[0019] Hereinafter, embodiments of a pressure-sensitive adhesive layer for a flexible image display device, a laminate for a flexible image display device, and a flexible image display device according to the present invention will be described in detail with reference to the drawings and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a cross-sectional view showing a conventional organic EL display device.

[0021] Figure 2 It is a cross-sectional view showing a flexible image display device according to another embodiment of the present invention.

[0022] Figure 3 This is a cross-sectional view showing an evaluation sample used in Examples.

[0023] Figure 4 It is a figure which shows the measuring method of flexural strength.

[0024] Explanation of symbols

[0025] 1 Polarizing film

[0026] 2. Protective film

[0027] 2-1 Protective film

[0028] 2-2 Protective film

[0029] 3 Phase difference layer

[0030] 4-1 Transparent conductive film

[0031] 4-2 Transparent conductive film

[0032] 5-1 Base film

[0033] 5-2 Base film

[0034] 6-1 Transparent conductive layer

[0035] 6-2 Transparent conductive layer

[0036] 7. Pads

[0037] 8Transparent substrate

[0038] 10Organic EL display panel

[0039] 10-1 Organic EL display panel with built-in touch panel

[0040] 11 Laminated body for flexible image display device (laminated body for organic EL display device)

[0041] 12 Adhesive layer

[0042] 12-1 1st adhesive layer

[0043] 12-2 Second adhesive layer

[0044] 13Decorative printing film

[0045] 20 optical laminate

[0046] 30 Touch Panel

[0047] 40 windows

[0048] 100Flexible image display device (organic EL display device) DETAILED DESCRIPTION

[0049] [Laminate for flexible image display device]

[0050] Preferably, the laminate for a flexible image display device of the present invention has a laminate for a flexible image display, wherein the laminate for a flexible image display has (is laminated with) an adhesive layer for a flexible image display device, a protective film formed of a transparent resin material, and a polarizing film in sequence at least on the visible side. In this structure, a phase difference film or the like may also be appropriately provided.

[0051] The thickness of the flexible image display laminate is preferably 92 μm or less, more preferably 60 μm or less, and further preferably 10 to 50 μm. When the thickness is within the above range, bending is not hindered, which is a preferred embodiment.

[0052] The polarizing film preferably has a protective film on at least one side of the polarizing film, and is preferably bonded by an adhesive layer. As the adhesive forming the adhesive layer, examples include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latexes, water-based polyesters, etc. The adhesive is usually used as an adhesive formed by an aqueous solution, usually containing 0.5~60% by weight of solid components. In addition to the above, as adhesives for polarizing films and protective films, UV-curing adhesives, electron beam-curing adhesives, etc. can be listed. Electron beam-curing polarizing film adhesives show suitable adhesion to the various protective films mentioned above. In addition, the adhesive used in the present invention may contain a metal compound filler. It should be noted that in the present invention, the material formed by bonding the polarizing film and the protective film by an adhesive (layer) is sometimes referred to as a polarizing film (polarizer).

[0053] <Polarizing Film>

[0054] The polarizing film (also called polarizer) that can be used in the present invention may be a polyvinyl alcohol (PVA)-based resin stretched by a stretching process such as in-air stretching (dry stretching) or in a boric acid aqueous solution and oriented with iodine.

[0055] As a representative method for manufacturing a polarizing film, there is a method (single-layer stretching method) including the steps of dyeing and stretching a single layer of a PVA-based resin as described in Japanese Patent Publication No. 2004-341515. In addition, there can be cited the method including the steps of stretching and dyeing a PVA-based resin layer and a stretching resin substrate in a laminated state as described in Japanese Patent Publication No. 51-069644, Japanese Patent Publication No. 2000-338329, Japanese Patent Publication No. 2001-343521, International Publication No. 2010 / 100917, Japanese Patent Publication No. 2012-073563, and Japanese Patent Publication No. 2011-2816. According to this method, even if the PVA-based resin layer is thin, it can be stretched without causing undesirable conditions such as breakage due to stretching because it is supported by the stretching resin substrate.

[0056] In the method for preparing a process of stretching in a laminated body and a process of dyeing, there is a stretching (dry stretching) method in a gas atmosphere as described in the above-mentioned Japanese Patent Publication No. 51-069644, Japanese Patent Publication No. 2000-338329, and Japanese Patent Publication No. 2001-343521. In addition, from the perspective of being able to stretch at a high ratio and improve polarization performance, it is preferred to prepare a process of stretching in a boric acid aqueous solution as described in International Publication No. 2010 / 100917 and Japanese Patent Publication No. 2012-073563, and it is particularly preferred to prepare a process of auxiliary stretching in a gas atmosphere before stretching in a boric acid aqueous solution as described in Japanese Patent Publication No. 2012-073563 (two-step stretching method). In addition, it is also preferred to stretch the PVA resin layer and the stretching resin substrate in the state of a laminate, over-dye the PVA resin layer, and then decolorize it as described in Japanese Patent Gazette No. 2011-2816 (over-dyeing and decolorizing method). The polarizing film used in the present invention can be a polarizing film formed by orienting iodine with a polyvinyl alcohol resin as described above, and stretched by a two-step stretching process consisting of auxiliary stretching in a gas atmosphere and stretching in a boric acid aqueous solution. In addition, the polarizing film used in the present invention can be a polarizing film formed by orienting iodine with a polyvinyl alcohol resin as described above, and the laminate of the stretched PVA resin layer and the stretching resin substrate is over-dyed and then decolorized.

[0057] The thickness of the polarizing film used in the present invention is preferably 12 μm or less, more preferably 9 μm or less, further preferably 1 to 8 μm, and particularly preferably 3 to 6 μm. When the thickness is within the above range, bending is not inhibited, which is a preferred embodiment.

[0058] <Phase difference film>

[0059] The retardation film (also referred to as retardation film) that can be used for the optical laminate of the present invention can be a film obtained by stretching a polymer film or a film obtained by orienting and fixing a liquid crystal material. In this specification, the retardation film refers to a film having birefringence in the plane and / or thickness direction.

[0060] Examples of the phase difference film include anti-reflection phase difference films (see Japanese Patent Application Publication Nos. 2012-133303

[0221] ,

[0222] , and

[0228] ), viewing angle compensation phase difference films (see Japanese Patent Application Publication Nos. 2012-133303

[0225] and

[0226] ), and tilted orientation phase difference films for viewing angle compensation (see Japanese Patent Application Publication No. 2012-133303

[0227] ).

[0061] The retardation film is not particularly limited in terms of, for example, retardation value, arrangement angle, three-dimensional birefringence, single layer or multilayer, etc., as long as it substantially has the above-mentioned functions, and a known retardation film can be used.

[0062] The absolute value C (m 2 / N) is 2×10 -12 ~100×10 -12 (m 2 / N), preferably 2×10 -12 ~50×10 -12 (m 2 / N). It is possible to prevent the phase difference value from changing due to the contraction stress of the polarizing film, the heat of the display panel, and the surrounding environment (humidity resistance / heat resistance) exerting force on the phase difference film. As a result, a display panel device with good display uniformity can be obtained. The C of the phase difference film is preferably 3×10 -12 ~45×10 -12 , particularly preferably 10×10 -12 ~40×10 -12 By setting C to the above range, the change and unevenness of the phase difference value when a force is applied to the phase difference film can be reduced. In addition, the photoelastic coefficient and Δn are easily in a compromise relationship. When the photoelastic coefficient is within this range, the display quality can be guaranteed without reducing the phase difference visibility.

[0063] In one embodiment, the retardation film of the present invention is produced by stretching and orienting a polymer film.

[0064] As the above-mentioned method for stretching the polymer film, any suitable stretching method can be adopted according to the purpose. As the above-mentioned stretching method suitable for the present invention, for example: a transverse uniaxial stretching method, a longitudinal and transverse simultaneous biaxial stretching method, a longitudinal and transverse stepwise biaxial stretching method, etc. can be cited. As a device for stretching, any suitable stretching machine such as a tenter stretching machine and a biaxial stretching machine can be used. Preferably, the above-mentioned stretching machine has a temperature control mechanism. When heating and stretching, the internal temperature of the stretching machine can be continuously changed or continuously changed. The process can be divided into 1 or more than 2 times. The stretching direction can be stretched along the film width direction (TD direction) or the oblique direction.

[0065] In the oblique stretching, the unstretched resin film is fed in the length direction and continuously stretched in a direction forming an angle within the above-mentioned specific range with the width direction. Thus, a long strip phase difference film can be obtained in which the angle (orientation angle θ) formed between the width direction of the film and the slow axis is within the above-mentioned specific range.

[0066] As the method for oblique stretching, as long as it can be stretched continuously along the direction of the above-mentioned specific range angle with the width direction of the unstretched resin film and form a slow axis in the direction of the angle of the above-mentioned specific range with the width direction of the film, there is no particular restriction. Any suitable method can be adopted from the existing known stretching methods such as Japanese Patent Publication No. 2005-319660, Japanese Patent Publication No. 2007-30466, Japanese Patent Publication No. 2014-194482, Japanese Patent Publication No. 2014-199483, Japanese Patent Publication No. 2014-199483.

[0067] In addition, as another embodiment, the following phase difference film can be used: a phase difference film obtained by bonding single sheets using a polycycloolefin film, a polycarbonate film, etc., using an acrylic adhesive in such a manner that the angle formed by the absorption axis of the polarizer and the slow axis of the 1 / 2 wavelength plate is 15°, and the angle formed by the absorption axis of the polarizer and the slow axis of the 1 / 4 wavelength plate is 75°.

[0068] In other embodiments, a phase difference film formed by stacking phase difference layers made by orienting and fixing liquid crystal materials can be used. Each phase difference layer can be an oriented solidified layer of a liquid crystal compound. By using a liquid crystal compound, the difference between nx and ny of the obtained phase difference layer can be greatly increased compared to a non-liquid crystal material, so the thickness of the phase difference layer used to obtain the desired in-plane phase difference can be greatly reduced. As a result, further thinning of the circular polarizer (ultimately a flexible image display device) can be achieved. In this specification, an "oriented solidified layer" refers to a layer in which a liquid crystal compound is oriented in a given direction within a layer and its orientation state is fixed. In this embodiment, a representative rod-shaped liquid crystal compound is oriented in a state parallel to the slow axis direction of the phase difference layer (uniform orientation). As a liquid crystal compound, for example: a liquid crystal compound (nematic liquid crystal) whose liquid crystal phase is a nematic phase. As such a liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer can be used. The manifestation mechanism of the liquid crystal properties of the liquid crystal compound can be either lyotropic or thermotropic. Liquid crystal polymers and liquid crystal monomers can be used alone or in combination.

[0069] The orientation solidification layer of the liquid crystal compound can be formed by the following method: an orientation treatment is applied to the surface of a given substrate, a coating liquid containing a liquid crystal compound is applied to the surface, the liquid crystal compound is oriented in a direction corresponding to the above-mentioned orientation treatment, and the orientation state is fixed. In one embodiment, the substrate is any suitable resin film, and the orientation solidification layer formed on the substrate can be transferred to the surface of the polarizing film. At this time, it is configured in a manner that the angle between the absorption axis of the polarizing film and the slow axis of the liquid crystal orientation solidification layer is 15°. Moreover, the phase difference of the liquid crystal orientation solidification layer is λ / 2 (about 270nm) for a wavelength of 550nm. In addition, as described above, a liquid crystal orientation solidification layer with a wavelength of λ / 4 (about 140nm) for 550nm is formed on a transferable substrate, and on the 1 / 2 wavelength plate side of the laminate of the polarizing film and the 1 / 2 wavelength plate, the absorption axis of the polarizing film and the slow axis of the 1 / 4 wavelength plate are stacked in a manner that the angle is 75°.

[0070] As the above-mentioned orientation treatment, any suitable orientation treatment can be adopted. Specifically, mechanical orientation treatment, physical orientation treatment, and chemical orientation treatment can be cited. Specific examples of mechanical orientation treatment include friction treatment and stretching treatment. Specific examples of physical orientation treatment include magnetic field orientation treatment and electric field orientation treatment. Specific examples of chemical orientation treatment include oblique evaporation method and optical orientation treatment. The treatment conditions of various orientation treatments can adopt any suitable conditions according to the purpose.

[0071] The thickness of the retardation film used in the present invention is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, and particularly preferably 3 to 8 μm. Within the above range, bending is not inhibited, which is a preferred embodiment.

[0072] <Protective film>

[0073] The protective film of the transparent resin material used in the present invention (also referred to as a transparent protective film) may be made of cycloolefin resins such as norbornene resins, olefin resins such as polyethylene and polypropylene, polyester resins, (meth)acrylic resins, and the like.

[0074] The thickness of the protective film used in the present invention is preferably 5 to 60 μm, more preferably 10 to 40 μm, and even more preferably 10 to 30 μm, and a surface treatment layer such as an anti-glare layer or an anti-reflection layer may be appropriately provided. When the thickness is within the above range, bending is not hindered, which is a preferred embodiment.

[0075] [Adhesive layer]

[0076] The pressure-sensitive adhesive layer for a flexible image display device of the present invention (may be simply referred to as a pressure-sensitive adhesive layer) is preferably disposed on the side opposite to the surface of the protective film that contacts the polarizing film.

[0077] In the adhesive layer for the flexible image display device of the present invention, an adhesive composition containing a (meth) acrylic polymer can be used. As long as the weight average molecular weight (Mw) of the above polymer is 1 million to 2.5 million and the glass transition temperature (Tg) is below 0°C, it can be used without particular limitation. For example, two or more of rubber adhesives, vinyl alkyl ether adhesives, silicone adhesives, polyester adhesives, polyamide adhesives, urethane adhesives, fluorine-containing adhesives, epoxy adhesives, polyether adhesives, etc. can be used in combination. Among them, from the viewpoints of transparency, processability, durability, adhesion, bending resistance, etc., it is preferred to use an acrylic adhesive alone.

[0078] <(Meth)acrylic polymer>

[0079] The adhesive layer for a flexible image display device of the present invention is characterized in that it is formed by an adhesive composition containing a (meth) acrylic polymer. When an acrylic adhesive is used as the above-mentioned adhesive composition, it is preferably a (meth) acrylic polymer containing a (meth) acrylic monomer having a linear or branched alkyl group with 1 to 24 carbon atoms as a monomer unit. By using the above-mentioned (meth) acrylic monomer having a linear or branched alkyl group with 1 to 24 carbon atoms, an adhesive layer with excellent bendability can be obtained. It should be noted that the (meth) acrylic polymer in the present invention refers to an acrylic polymer and / or a methacrylic polymer, and in addition, (meth) acrylate refers to acrylate and / or methacrylate.

[0080] Specific examples of the (meth)acrylic monomer having a linear or branched alkyl group having 1 to 24 carbon atoms constituting the main skeleton of the (meth)acrylic polymer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethyl (meth)acrylate, The (meth)acrylate monomers include hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, etc. Among them, monomers with a low glass transition temperature (Tg) generally become viscoelastic even in a lower temperature range, so from the viewpoint of bendability, (meth)acrylic acid monomers having a linear or branched alkyl group with 4 to 8 carbon atoms are preferred. As the above (meth)acrylic acid monomers, one or more kinds can be used.

[0081] The (meth)acrylic monomer having a linear or branched alkyl group having 1 to 24 carbon atoms is the main component of all monomers constituting the (meth)acrylic polymer. Here, the main component means that the (meth)acrylic monomer having a linear or branched alkyl group having 1 to 24 carbon atoms is preferably 70 to 100% by weight, more preferably 80 to 99.9% by weight, further preferably 85 to 99.9% by weight, and particularly preferably 90 to 99.8% by weight of all monomers constituting the (meth)acrylic polymer.

[0082] As the monomer unit constituting the above-mentioned (meth) acrylic polymer, it is preferred to contain a (meth) acrylic polymer, wherein the (meth) acrylic polymer contains a hydroxyl-containing monomer having a reactive functional group. By using the above-mentioned hydroxyl-containing monomer, an adhesive layer having excellent adhesion and bendability can be obtained. The above-mentioned hydroxyl-containing monomer is a compound containing a hydroxyl group in its structure and containing polymerizable unsaturated double bonds such as a (meth) acryloyl group and a vinyl group.

[0083] As specific examples of the above-mentioned hydroxyl-containing monomers, for example, (meth) 2-hydroxyethyl acrylate, (meth) 3-hydroxypropyl acrylate, (meth) 4-hydroxybutyl acrylate, (meth) 6-hydroxyhexyl acrylate, (meth) 8-hydroxyoctyl acrylate, (meth) 10-hydroxydecyl acrylate, (meth) 12-hydroxylauryl acrylate and other (meth) hydroxyalkyl acrylates, methacrylate 4-hydroxymethylcyclohexyl acrylate and the like can be cited. Among the above-mentioned hydroxyl-containing monomers, from the viewpoint of durability and adhesion, (meth) 2-hydroxyethyl acrylate and (meth) 4-hydroxybutyl acrylate are preferred. It should be noted that, as the above-mentioned hydroxyl-containing monomers, one or more kinds can be used.

[0084] The (meth)acrylic polymer may contain monomers such as carboxyl group-containing monomers, amino group-containing monomers, and amide group-containing monomers having a reactive functional group as monomer units, and the use of these monomers is preferred from the viewpoint of adhesion in a hot and humid environment.

[0085] As the monomer unit constituting the above-mentioned (meth) acrylic polymer, a (meth) acrylic polymer may be contained, wherein the (meth) acrylic polymer comprises a carboxyl-containing monomer having a reactive functional group. By using the above-mentioned carboxyl-containing monomer, an adhesive layer having excellent adhesion under a hot and humid environment can be obtained. The above-mentioned carboxyl-containing monomer is a compound containing a carboxyl group in its structure and containing polymerizable unsaturated double bonds such as a (meth) acryloyl group and a vinyl group.

[0086] Specific examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and the like.

[0087] As the monomer unit constituting the above-mentioned (meth) acrylic polymer, a (meth) acrylic polymer may be contained, and the (meth) acrylic polymer may contain an amino-containing monomer having a reactive functional group. By using the above-mentioned amino-containing monomer, an adhesive layer having excellent adhesion in a hot and humid environment may be obtained. The above-mentioned amino-containing monomer is a compound containing an amino group in its structure and containing a polymerizable unsaturated double bond such as a (meth) acryloyl group and a vinyl group.

[0088] Specific examples of the amino group-containing monomer include N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate.

[0089] As the monomer unit constituting the above-mentioned (meth) acrylic polymer, a (meth) acrylic polymer may be contained, and the (meth) acrylic polymer may contain an amide group-containing monomer having a reactive functional group. By using the above-mentioned amide group-containing monomer, an adhesive layer having excellent adhesion may be obtained. The above-mentioned amide group-containing monomer is a compound containing an amide group in its structure and containing polymerizable unsaturated double bonds such as a (meth) acryloyl group and a vinyl group.

[0090] Specific examples of the amide group-containing monomers include: acrylamide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-hydroxymethyl-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl-containing lactam monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam.

[0091] As a monomer unit constituting the (meth)acrylic polymer, the blending ratio (total amount) of the monomer having a reactive functional group in all monomers constituting the (meth)acrylic polymer is preferably 20 wt% or less, more preferably 10 wt% or less, further preferably 0.01 to 8 wt%, particularly preferably 0.01 to 5 wt%, and most preferably 0.05 to 3 wt%. When it exceeds 20 wt%, the number of crosslinking sites increases, the flexibility of the adhesive (layer) is lost, and therefore, there is a tendency that stress relaxation properties become poor.

[0092] As the monomer units constituting the above-mentioned (meth) acrylic polymer, in addition to the above-mentioned monomers having reactive functional groups, other comonomers may be introduced within the scope that does not impair the effect of the present invention. The proportion thereof is not particularly limited, and is preferably 30% by weight or less, and more preferably not contained, in all monomers constituting the above-mentioned (meth) acrylic polymer. When it is greater than 30% by weight, especially when other than (meth) acrylic monomers are used, the reaction sites with the film are reduced, and there is a tendency for the adhesion to be reduced.

[0093] In the present invention, when using the above-mentioned (meth) acrylic polymer, a polymer with a weight average molecular weight (Mw) of 1 million to 2.5 million is generally used. Considering durability, especially heat resistance and bendability, it is preferably 1.2 million to 2.2 million, and more preferably 1.4 million to 2 million. When the weight average molecular weight is less than 1 million, in order to ensure durability, when the polymer chains are cross-linked with each other, compared with the polymer with a weight average molecular weight of more than 1 million, the cross-linking sites increase, and the flexibility of the adhesive (layer) is lost. Therefore, the dimensional changes of the outer side (convex side) and the inner side (concave side) of the bend generated between each film during bending cannot be relaxed, and the film is prone to breakage. In addition, when the weight average molecular weight is greater than 2.5 million, in order to adjust to the viscosity for coating, a large amount of diluting solvent is required, and the cost is increased, so it is not preferred. In addition, the entanglement between the polymer chains of the obtained (meth) acrylic polymer becomes complicated, so the flexibility is poor, and the film is prone to breakage when bending. In addition, the weight average molecular weight (Mw) is a value measured by GPC (gel permeation chromatography) and calculated by polystyrene conversion.

[0094] Such (meth)acrylic polymers can be produced by appropriately selecting known production methods such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The obtained (meth)acrylic polymers may be any copolymer such as a random copolymer, a block copolymer, or a graft copolymer.

[0095] In the solution polymerization, ethyl acetate, toluene, etc. can be used as the polymerization solvent. As a specific example of solution polymerization, it is usually carried out under the reaction conditions of about 50-70° C. and about 5-30 hours with the addition of a polymerization initiator under an inert gas flow such as nitrogen.

[0096] There is no particular limitation on the polymerization initiator, chain transfer agent, emulsifier, etc. used in the free radical polymerization, and they can be appropriately selected and used. It should be noted that the weight average molecular weight of the (meth)acrylic polymer can be controlled by the amount of the polymerization initiator and chain transfer agent and the reaction conditions, and the amount can be appropriately adjusted according to the type.

[0097] Examples of the polymerization initiator include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2-methylpropylamidine) disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropylamidine] hydrate (trade name: VA-057, manufactured by Wako Pure Chemical Industries, Ltd.), persulfates such as potassium persulfate and ammonium persulfate, di(2-ethylhexyl) peroxydicarbonate, and peroxydicarbonate. The initiators include, but are not limited to, peroxide initiators such as di(4-tert-butylcyclohexyl) dicarbonate, di-sec-butyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, dibenzoyl peroxide, tert-butyl peroxyisobutyrate, 1,1-di(tert-hexylperoxide)cyclohexane, tert-butyl hydroperoxide, hydrogen peroxide, and redox initiators obtained by combining peroxides with reducing agents, such as combinations of persulfates and sodium bisulfite, and combinations of peroxides and sodium ascorbate.

[0098] The polymerization initiator may be used alone or in combination of two or more. For example, the total content is preferably about 0.005 to 1 part by weight, more preferably about 0.02 to 0.5 part by weight, based on 100 parts by weight of all monomers constituting the (meth)acrylic polymer.

[0099] In addition, when a chain transfer agent, an emulsifier used in emulsion polymerization, or a reactive emulsifier is used, these can be appropriately used. In addition, as their addition amount, they can be appropriately determined within the range that does not impair the effect of the present invention.

[0100] <Crosslinking agent>

[0101] The adhesive composition of the present invention may contain a crosslinking agent. As the crosslinking agent, an organic crosslinking agent or a polyfunctional metal chelate may be used. As the organic crosslinking agent, isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, imine crosslinking agents, etc. may be cited. Polyfunctional metal chelates are formed by covalent bonding or coordination bonding of polyvalent metals and organic compounds. As polyvalent metal atoms, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. may be cited. As atoms in organic compounds that are covalently bonded or coordinately bonded, oxygen atoms may be cited, and as organic compounds, alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, ketone compounds, etc. may be cited. Among them, isocyanate crosslinking agents (especially trifunctional isocyanate crosslinking agents) are preferred from the aspect of durability, and peroxide crosslinking agents and isocyanate crosslinking agents (especially difunctional isocyanate crosslinking agents) are preferred from the aspect of bendability. Peroxide crosslinking agents and difunctional isocyanate crosslinking agents both form soft two-dimensional crosslinking, while trifunctional isocyanate crosslinking agents form more solid three-dimensional crosslinking. When bending, two-dimensional crosslinking as a softer crosslinking is advantageous. However, in the case of only two-dimensional crosslinking, durability is lacking and peeling is likely to occur, so the mixed crosslinking of two-dimensional crosslinking and three-dimensional crosslinking is good, so the combination of trifunctional isocyanate crosslinking agents and peroxide crosslinking agents and difunctional isocyanate crosslinking agents is a preferred method.

[0102] For example, the amount of the crosslinking agent used is preferably 0.01 to 5 parts by mass, more preferably 0.03 to 2 parts by mass, and more preferably less than 0.03 to 1 part by mass relative to 100 parts by mass of the (meth)acrylic polymer. When within the above range, the bending resistance is excellent, which is a preferred embodiment.

[0103] <Other additives>

[0104] The adhesive composition of the present invention may further contain other known additives, such as various silane coupling agents, polyether compounds such as polyalkylene glycols such as polypropylene glycol, colorants, pigment powders, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, antistatic agents (alkali metal salts as ionic compounds, ionic liquids, etc.), inorganic or organic fillers, metal powders, granular, foil-like materials, etc. In addition, redox-type materials with the addition of a reducing agent may be used within a controllable range.

[0105] It should be noted that, in the case where the adhesive layer for a flexible image display device further has an adhesive layer, these adhesive layers may be layers having the same composition (same adhesive composition) and the same properties, or layers having different properties, without particular limitation. In the case of having multiple adhesive layers, it is required that the storage modulus G' of the adhesive layer on the outermost surface of the convex side at 25°C when the above-mentioned laminate is bent is substantially the same as the storage modulus G' of other adhesive layers at 25°C, or less than the storage modulus G' of other adhesive layers at 25°C. From the viewpoint of operability, economy, and bendability, all adhesive layers are preferably adhesive layers having substantially the same composition and the same properties. In addition, substantially the same means that the difference in the storage modulus (G') between the adhesive layers is within the range of ±15% relative to the average value of the storage modulus (G') of the multiple adhesive layers, preferably within the range of ±10%.

[0106] <Formation of Adhesive Layer>

[0107] The adhesive layer in the present invention is preferably formed by the above-mentioned adhesive composition. As a method for forming the adhesive layer, for example, the above-mentioned adhesive composition is applied to a separator that has been subjected to a peeling treatment, and the polymerization solvent is dried and removed to form the adhesive layer. In addition, it can also be prepared by applying the above-mentioned adhesive composition on a polarizing film, etc., and drying and removing the polymerization solvent, etc. to form an adhesive layer on the polarizing film, etc. It should be noted that when applying the adhesive composition, one or more solvents other than the polymerization solvent can also be appropriately added.

[0108] As the separator subjected to the release treatment, a silicone release liner is preferably used. When the adhesive composition of the present invention is applied to such a liner and dried to form an adhesive layer, as a method for drying the adhesive, a suitable method can be appropriately adopted according to the purpose. It is preferred to use a method of heating and drying the above-mentioned coated film. The heating and drying temperature is preferably 40 to 200°C, more preferably 50 to 180°C, and particularly preferably 70 to 170°C. By setting the heating temperature to the above range, an adhesive having excellent adhesive properties can be obtained.

[0109] The drying time may be any appropriate time, and the drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 10 minutes, and particularly preferably 10 seconds to 5 minutes.

[0110] As the coating method of the above-mentioned adhesive composition, various methods can be used. Specifically, for example, roll coating, lick roller coating, gravure coating, reverse coating, roller brushing, spray coating, dip roll coating, rod coating, blade coating, air knife coating, curtain coating, die lip coating, extrusion coating using a die coater, etc. can be cited.

[0111] The thickness of the adhesive layer for the flexible image display device of the present invention is preferably 5 to 150 μm, more preferably 15 to 100 μm. The adhesive layer can be a single layer or can have a laminated structure. When it is within the above range, it will not hinder bending, and from the viewpoint of adhesion (resistance to retention), it is also a preferred mode. When it is greater than 150 μm, when it is repeatedly bent, the polymer chains in the adhesive layer become easy to move, and the degradation becomes serious. Therefore, there is a hidden danger of peeling. When it is less than 5 μm, the stress during bending cannot be relaxed, and there is a hidden danger of fracture. In addition, when there are multiple adhesive layers, it is preferred that all the adhesive layers are within the above range.

[0112] The glass transition temperature (Tg) of the adhesive layer for the flexible image display device of the present invention is below 0°C, preferably below -20°C, and more preferably below -25°C. It should be noted that the lower limit of Tg is preferably above -50°C, and more preferably above -45°C. If the Tg of the adhesive layer is within such a range, the adhesive layer is not easy to harden when bent in a low temperature environment, and has excellent stress relaxation properties, so that the peeling of the adhesive layer and the breakage of the polarizing film can be suppressed, and a bendable or foldable flexible image display device can be realized.

[0113] The storage modulus (G') of the adhesive layer for a flexible image display device of the present invention is preferably 1.0 MPa or less, more preferably 0.8 MPa or less, and further preferably 0.3 MPa or less at 25°C. In addition, it is preferably 1.5 MPa or less, more preferably 1.0 MPa or less, and further preferably 0.5 MPa or less at -20°C. When the storage modulus of the adhesive layer is within such a range, the adhesive layer is not easy to harden, and has excellent stress relaxation properties and excellent bending resistance, so that a bendable or foldable flexible image display device can be realized.

[0114] The adhesive force of the adhesive layer for the flexible image display device of the present invention to the polarizer is preferably 5~40N / 25mm, more preferably 8~38N / 25mm, and further preferably 10~36N / 25mm. When the adhesive force of the adhesive layer is within such a range, the adhesion is excellent, and it will not peel off for repeated bending, and a flexible or foldable image display device can be realized. It should be noted that, for the above-mentioned adhesive force, no matter what kind of polarizer, as long as it is included in the above-mentioned range, it is a preferred mode. It should be noted that, as the adhesive force to the polarizer, for example, a tensile tester (AutographSHIMAZU AG-1 10KN) can be used to measure the adhesive force (N / 25mm) when peeling at a peeling angle of 180° and a peeling speed of 300mm / min.

[0115] The total light transmittance of the pressure-sensitive adhesive layer for a flexible image display device of the present invention in the visible light wavelength region (based on JIS K7136) is preferably 85% or more, more preferably 90% or more.

[0116] The haze (based on JIS K7136) of the pressure-sensitive adhesive layer for a flexible image display device of the present invention is preferably 3.0% or less, more preferably 2.0% or less.

[0117] In addition, the said total light transmittance and the said haze can be measured using the haze meter (made by Murakami Color Research Laboratory, trade name "HM-150"), for example.

[0118] [Transparent conductive layer]

[0119] In order to further impart a touch sensor function, etc., it is preferred that a transparent conductive layer sandwiching the adhesive layer of the present invention is provided in the laminate for the flexible image display device of the present invention. The member having the transparent conductive layer is not particularly limited, and a known member can be used, and examples thereof include a member having a transparent conductive layer on a transparent substrate such as a transparent film, and a member having a transparent conductive layer and a liquid crystal cell.

[0120] As the transparent substrate, any substrate having transparency may be used, and examples thereof include substrates formed of resin films (e.g., sheet-shaped, film-shaped, plate-shaped substrates, etc.). The thickness of the transparent substrate is not particularly limited, but is preferably about 10 to 200 μm, more preferably about 15 to 150 μm.

[0121] The material of the resin film is not particularly limited, and various plastic materials with transparency can be cited. For example, the material thereof includes polyester resins such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, polyphenylene sulfide resins, etc. Among them, polyester resins, polyimide resins and polyethersulfone resins are particularly preferred.

[0122] In addition, the surface of the transparent substrate may be subjected to etching treatment or primer treatment such as sputtering, corona discharge, flame, ultraviolet irradiation, electron beam irradiation, chemical conversion, oxidation, etc. in advance to improve the adhesion of the transparent conductive layer disposed thereon to the transparent substrate. In addition, before the transparent conductive layer is disposed, dust removal and purification may be performed by solvent cleaning, ultrasonic cleaning, etc. as needed.

[0123] As the constituent material of the above-mentioned transparent conductive layer, there is no particular limitation, and a metal oxide of at least one metal selected from indium, tin, zinc, gallium, antimony, titanium, silicon, zirconium, magnesium, aluminum, gold, silver, copper, palladium, and tungsten can be used. The metal oxide can further contain the metal atoms shown above as needed. For example, indium oxide (ITO) containing tin oxide, tin oxide containing antimony, etc. are preferably used, and ITO is particularly preferably used. As ITO, it is preferably containing 80 to 99% by weight of indium oxide and 1 to 20% by weight of tin oxide.

[0124] Examples of the ITO include crystalline ITO and amorphous (amorphous) ITO. Crystalline ITO can be obtained by applying a high temperature during sputtering or further heating amorphous ITO.

[0125] The thickness of the transparent conductive layer of the present invention is preferably 0.005 to 10 μm, more preferably 0.01 to 3 μm, and further preferably 0.01 to 1 μm. When the thickness of the transparent conductive layer is less than 0.005 μm, there is a tendency for the change in the resistance value of the transparent conductive layer to increase. On the other hand, when the thickness is greater than 10 μm, there is a tendency for the productivity of the transparent conductive layer to decrease, the cost to increase, and the optical properties to decrease.

[0126] The total light transmittance of the transparent conductive layer of the present invention is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.

[0127] The density of the transparent conductive layer of the present invention is preferably 1.0 to 10.5 g / cm 3 , more preferably 1.3 to 3.0 g / cm 3 .

[0128] The surface resistance value of the transparent conductive layer of the present invention is preferably 0.1 to 1000 Ω / □, more preferably 0.5 to 500 Ω / □, and further preferably 1 to 250 Ω / □.

[0129] The method for forming the transparent conductive layer is not particularly limited, and a conventionally known method can be used. Specifically, examples thereof include vacuum evaporation, sputtering, and ion plating. In addition, an appropriate method can be used depending on the desired film thickness.

[0130] Furthermore, if necessary, a primer layer, an oligomer-preventing layer, or the like may be provided between the transparent conductive layer and the transparent substrate.

[0131] The transparent conductive layer constitutes a touch sensor and is required to be bendable.

[0132] Furthermore, when the transparent conductive layer is used in a flexible image display device, it can be suitably applied to a so-called in-cell or out-cell type liquid crystal display device having a built-in touch sensor, and in particular, a touch sensor can be built-in (installed) in an organic EL display panel.

[0133] [Conductive layer (antistatic layer)]

[0134] In addition, the laminate for the flexible image display device of the present invention may also include a conductive layer (conductive layer, antistatic layer). The above-mentioned laminate for the flexible image display device has a bending function and becomes a very thin structure. Therefore, it is highly reactive to weak static electricity generated in the manufacturing process, etc. and is easily damaged. However, by providing a conductive layer on the above-mentioned laminate, the burden caused by static electricity in the manufacturing process, etc. can be greatly reduced, which is a preferred method.

[0135] In addition, one of the characteristics of the flexible image display device including the above-mentioned laminate is that it has a bending function, but when it is bent continuously, static electricity may be generated due to the contraction between the films (substrates) in the bent portion. Therefore, when the above-mentioned laminate is given conductivity, the generated static electricity can be quickly removed, and the damage caused by static electricity to the image display device can be reduced, which is a preferred method.

[0136] In addition, the conductive layer may be a primer layer having a conductive function, an adhesive containing a conductive component, or a surface treatment layer containing a conductive component. For example, a method of forming a conductive layer between a polarizing film and an adhesive layer using an antistatic agent composition containing a conductive polymer such as polythiophene and an adhesive may be adopted. In addition, an adhesive containing an ionic compound as an antistatic agent may also be used. In addition, the conductive layer preferably has one or more layers, and may also contain two or more layers.

[0137] [Flexible image display device]

[0138] The flexible image display device of the present invention comprises the above-mentioned laminate for flexible image display device and an organic EL display panel configured to be bendable, and the laminate for flexible image display device is arranged on the visible side of the organic EL display panel and configured to be bendable. In addition, a liquid crystal panel may be used instead of the organic EL display panel, and a window may be further arranged on the visible side of the laminate for flexible image display device.

[0139] The flexible image display device of the present invention can be suitably used as a flexible liquid crystal display device, an organic EL (electroluminescent) display device, a PDP (plasma display panel), an electronic paper or other image display device. In addition, it can be used regardless of the touch panel method such as a resistive film method or an electrostatic capacitance method.

[0140] In addition, as a flexible image display device of the present invention, Figure 2 As shown, the present invention can also be used as an in-cell type flexible image display device in which the transparent conductive layer 6 constituting the touch sensor is built into the organic EL display panel 10 .

[0141] Example

[0142] Below, several embodiments related to the present invention are described, but it is not intended that the present invention is limited to the mode shown in the above specific example. In addition, the numerical value in the table is the amount of compounding (addition amount), indicating the solid content or solid content ratio (weight basis). The content of compounding and the evaluation result are shown in Table 1 to Table 4.

[0143] [Example 1]

[0144] [Polarizing film]

[0145] As a thermoplastic resin substrate, an amorphous polyethylene terephthalate (hereinafter also referred to as "PET") (IPA copolymer PET) film (thickness: 100 μm) having 7 mol % of isophthalic acid units was prepared, and the surface was subjected to a corona treatment (58 W / m 2 / min). On the other hand, 1 wt% of PVA (polymerization degree 4200, saponification degree 99.2%) to which acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name: GOHSEFIMER Z200 (average polymerization degree: 1200, saponification degree: 98.5 mol%, acetoacetylation degree: 5 mol%) was added was prepared, and a coating liquid of a 5.5 wt% PVA aqueous solution of a PVA-based resin was prepared and applied so that the film thickness after drying would be 12 μm, and dried by hot air drying at 60° C. for 10 minutes to produce a laminate having a layer of the PVA-based resin provided on a substrate.

[0146] Next, the laminate is first free-end stretched to 1.8 times at 130°C in air (assisted stretching in gas atmosphere) to generate a stretched laminate. Next, the following process is performed: the PVA layer after the PVA molecules contained in the stretched laminate are oriented is insolubilized by immersing the stretched laminate in a boric acid insolubilizing aqueous solution at a liquid temperature of 30°C for 30 seconds. In the boric acid insolubilizing aqueous solution of this process, the boric acid content is set to 3 parts by mass relative to 100 parts by mass of water. A colored laminate is generated by dyeing the stretched laminate. The colored laminate is obtained by immersing the stretched laminate in a dyeing solution containing iodine and potassium iodide at a liquid temperature of 30°C for any period of time in such a way that the monomer transmittance of the PVA layer constituting the polarizing film finally generated reaches 40~44%, thereby dyeing the PVA layer contained in the stretched laminate with iodine. In this process, the dyeing liquid uses water as a solvent, the iodine concentration is set to a range of 0.1 to 0.4 weight %, and the potassium iodide concentration is set to a range of 0.7 to 2.8 weight %. The ratio of the concentration of iodine to potassium iodide is 1 to 7. Then, the following process is performed: the PVA molecules of the PVA layer adsorbed with iodine are cross-linked by immersing the colored laminate in a boric acid cross-linking aqueous solution at 30°C for 60 seconds. In the boric acid cross-linking aqueous solution of this process, the boric acid content is set to 3 mass parts relative to 100 mass parts of water, and the potassium iodide content is set to 3 mass parts relative to 100 mass parts of water.

[0147] Furthermore, in a boric acid aqueous solution, the obtained colored laminate was stretched to 3.05 times (stretched in a boric acid aqueous solution) at a stretching temperature of 70°C in the same direction as the previous stretching in the gas atmosphere, and an optical film laminate with a final stretching ratio of 5.50 times was obtained. The optical film laminate was taken out from the boric acid aqueous solution, and the boric acid attached to the surface of the PVA layer was washed with an aqueous solution, in which the potassium iodide content was 4 parts by mass relative to 100 parts by mass of water. The washed optical film laminate was dried by a warm air drying process at 60°C. The thickness of the polarizing film contained in the obtained optical film laminate was 5μm.

[0148] [Protective film]

[0149] As the protective film, a film obtained by extruding methacrylic resin particles having glutarimide ring units, molding them into a film shape, and then stretching them was used. The protective film had a thickness of 20 μm and a water vapor permeability of 160 g / m 2 Acrylic film.

[0150] Next, the polarizing film and the protective film were bonded together using the adhesive described below to prepare a polarizing film.

[0151] As the above-mentioned adhesive (active energy ray-curable adhesive), each component was mixed according to the formulation table described in Table 1, and stirred at 50° C. for 1 hour to prepare an adhesive (active energy ray-curable adhesive A). The numerical values ​​in the table represent weight % when the total amount of the composition is 100 weight %. The components used are as follows.

[0152] HEAA: Hydroxyethyl acrylamide

[0153] M-220: ARONIX M-220, tripropylene glycol diacrylate), manufactured by Toagosei Co., Ltd.

[0154] ACMO: Acryloylmorpholine

[0155] AAEM: 2-acetoacetoxyethyl methacrylate, manufactured by Nippon Synthetic Chemical Co., Ltd.

[0156] UP-1190: ARUFON UP-1190, manufactured by Toagosei Co., Ltd.

[0157] IRG907: IRGACURE907, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, manufactured by BASF

[0158] DETX-S: KAYACURE DETX-S, diethylthioxanthone, manufactured by Nippon Kayaku Co., Ltd.

[0159]

[0160] It should be noted that in the embodiments and comparative examples using the above-mentioned adhesive, after the above-mentioned protective film and the above-mentioned polarizing film were laminated by the adhesive, ultraviolet rays were irradiated to cure the adhesive to form an adhesive layer. The ultraviolet rays were irradiated using a gallium-encapsulated metal halide lamp (manufactured by Fusion UV Systems, Inc., trade name "LightHAMMER10", valve: V valve, maximum illumination: 1600mW / cm 2 , cumulative exposure 1000 / mJ / cm 2 (wavelength 380~440nm)).

[0161] <Preparation of (meth)acrylic polymer A1>

[0162] A monomer mixture containing 99 parts by mass of butyl acrylate (BA) and 1 part by mass of 4-hydroxybutyl acrylate (HBA) was placed in a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser.

[0163] Furthermore, 0.1 parts by mass of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with ethyl acetate to 100 parts by mass of the monomer mixture (solid content), nitrogen was introduced while slowly stirring to perform nitrogen replacement, and then the liquid temperature in the flask was maintained at around 55°C, and a polymerization reaction was performed for 7 hours. Then, ethyl acetate was added to the obtained reaction solution to prepare a solution of a (meth)acrylic polymer A1 having a weight average molecular weight of 1.6 million and adjusted to a solid content concentration of 30%.

[0164] <Preparation of Acrylic Adhesive Composition>

[0165] An acrylic adhesive composition was prepared by adding 0.1 parts by mass of an isocyanate crosslinking agent (trade name: Takenate D110N, trimethylolpropane xylylene diisocyanate, manufactured by Mitsui Chemicals, Inc.), 0.3 parts by mass of a peroxide crosslinking agent benzoyl peroxide (trade name: NYPER BMT, manufactured by NOF Corporation), and 0.08 parts by mass of a silane coupling agent (trade name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) to 100 parts by mass of the solid content of the obtained (meth)acrylic polymer A1 solution.

[0166] <Laminate with Adhesive Layer>

[0167] The acrylic adhesive composition was uniformly applied on the surface of a 38 μm thick polyethylene terephthalate film (PET film, separator) treated with a silicone release agent using a fountain coater, and dried in an air-circulating constant temperature oven at 155° C. for 2 minutes to form an adhesive layer with a thickness of 25 μm on the surface of the substrate.

[0168] Next, the separator on which the pressure-sensitive adhesive layer 1 was formed was transferred to the protective film side (corona-treated) of the obtained polarizing film to prepare a pressure-sensitive adhesive layer-attached laminate.

[0169] Then, if Figure 3 As shown, a 25 μm thick PET film (transparent substrate, manufactured by Mitsubishi Plastics Co., Ltd., trade name: Diafoil) subjected to a corona treatment was bonded to the surface of the laminate with an adhesive layer obtained as described above after the separator was peeled off, thereby producing a laminate for a flexible image display device.

[0170] <Preparation of (meth)acrylic polymer A5>

[0171] The polymerization reaction was carried out for 7 hours while maintaining the liquid temperature in the flask at approximately 55°C. The polymerization reaction was carried out in the same manner as in the preparation of the (meth)acrylic polymer A1 except that the mixing ratio (weight ratio) of ethyl acetate to toluene was 85 / 15.

[0172] <Preparation of (meth)acrylic polymer A6>

[0173] The polymerization reaction was carried out for 7 hours while maintaining the liquid temperature in the flask at approximately 55°C. The polymerization reaction was carried out in the same manner as in the preparation of the (meth)acrylic polymer A1 except that the mixing ratio (weight ratio) of ethyl acetate to toluene was 70 / 30.

[0174] [Examples 2 to 9, and Comparative Examples 1 to 2]

[0175] In Example 2 and the like, a laminate for a flexible image display device was produced in the same manner as in Example 1 except that changes were made as shown in Tables 2 to 4 when preparing the polymer ((meth)acrylic polymer) and the adhesive composition to be used unless otherwise noted.

[0176] The abbreviations in Tables 2 and 3 are as follows.

[0177] BA: n-butyl acrylate

[0178] 2EHA: 2-Ethylhexyl acrylate

[0179] AA: Acrylic acid

[0180] HBA: 4-Hydroxybutyl Acrylate

[0181] HEA: 2-Hydroxyethyl Acrylate

[0182] MMA: Methyl Methacrylate

[0183] ACMO: Acryloylmorpholine

[0184] PEA: Phenoxyethyl acrylate

[0185] NVP: N-vinyl pyrrolidone

[0186] D110N: trimethylolpropane / xylylene diisocyanate adduct (Mitsui Chemicals, Inc., trade name: Takenate D110N)

[0187] D160N: trimethylolpropane / hexamethylene diisocyanate (Mitsui Chemicals, Inc., trade name: Takenate D160N)

[0188] C / L: trimethylolpropane / toluene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name: Coronate L)

[0189] Peroxide: Benzoyl peroxide (peroxide crosslinking agent, manufactured by NOF Corporation, trade name: NYPER BMT)

[0190] [evaluate]

[0191] <Measurement of Weight Average Molecular Weight (Mw) of (Meth)Acrylic Polymer>

[0192] The weight average molecular weight (Mw) of the obtained (meth)acrylic polymer was measured by GPC (gel permeation chromatography).

[0193] Analysis device: HLC-8120GPC manufactured by Tosoh Corporation

[0194] Column: Made by Tosoh Corporation, G7000H XL +GMH XL +GMH XL

[0195] Column size: 7.8mmφ×30cm each, total 90cm

[0196] Column temperature: 40°C

[0197] Flow rate: 0.8ml / min

[0198] Injection volume: 100 μl

[0199] Eluent: Tetrahydrofuran

[0200] Detector: Differential Refractometer (RI)

[0201] Standard sample: polystyrene

[0202] (Measurement of thickness)

[0203] The thicknesses of the polarizing film, the protective film, the pressure-sensitive adhesive layer, and the transparent substrate were measured using a micrometer (manufactured by MITUTOYO CORPORATION) and determined by calculation.

[0204] (Measurement of Glass Transition Temperature Tg of Adhesive Layer)

[0205] The separator was peeled off from the surface of the adhesive layer of each embodiment and comparative example, and multiple adhesive layers were stacked to prepare a test sample with a thickness of about 1.5 mm. The test sample was punched into a disk with a diameter of 8 mm, sandwiched between parallel plates, and a dynamic viscoelasticity measuring device manufactured by TA Instruments, trade name "RSA III", was used to obtain the peak temperature of tan δ obtained by dynamic viscoelasticity measurement under the following measurement conditions.

[0206] (Measurement conditions)

[0207] Deformation mode: Twist

[0208] Measuring temperature: -40℃~150℃

[0209] Heating speed: 5℃ / min

[0210] (Bending test)

[0211] Figure 4 A schematic diagram of a 180° flexural strength tester (manufactured by Imoto Manufacturing Co., Ltd.) is shown in the figure. This device is a mechanism that clamps a mandrel in a constant temperature chamber and repeatedly bends a chuck on one side by 180°, and the bending radius can be changed by the diameter of the mandrel. It is a mechanism that stops the test when the film breaks. In the test, a 5cm×15cm flexible image display device laminate obtained by each embodiment and comparative example is set in the device, and the test is carried out under the conditions of a temperature of -20°C, a bending angle of 180°, a bending radius of 3mm, a bending speed of 1 second / time, and a weight of 100g. The flexural strength is evaluated based on the number of times the flexible image display device laminate breaks. Here, the test is stopped when the number of bends reaches 200,000 times.

[0212] In addition, the rupture of the film such as a polarizing film and the peeling of the adhesive layer at low temperature were evaluated by the folding resistance test at low temperature (-20°C).

[0213] In addition, as a measurement (evaluation) method, a laminate for a flexible image display device (refer to Figure 3 ) was bent with the polarizing film facing inward (concave side) and evaluated.

[0214] <Whether there is a break>

[0215] ○: No breakage

[0216] △: There is a slight break at the end of the bend (no problem in actual use)

[0217] ×: There is a crack on the entire surface of the bent portion (there is a problem in actual use)

[0218] <Existence of appearance (peeling)>

[0219] ○: No bending or peeling was observed

[0220] △: Slight bending / peeling of the bent portion was observed (no problem in actual use)

[0221] ×: The entire surface of the bent portion is confirmed to be bent / peeled off (there is a problem in actual use)

[0222]

[0223]

[0224]

[0225] From the evaluation results in Table 4, it was confirmed through the flexural resistance test that in all the examples, even in a low-temperature environment, the fracture and peeling were at a level that would not cause any problem in practical use.

[0226] On the other hand, in Comparative Example 1, it was confirmed that the (meth)acrylic polymer used had a small molecular weight and the glass transition temperature of the adhesive layer was high, so it was broken and peeled off in a low temperature environment, and it was not at a level that could be used in practice. In addition, in Comparative Example 2, it was confirmed that the (meth)acrylic polymer used had a large molecular weight, so it was broken and peeled off in a low temperature environment, similarly to Comparative Example 1, and it was not at a level that could be used in practice.

[0227] The present invention has been described above with reference to the accompanying drawings for specific embodiments, but the present invention may be modified in various ways in addition to the illustrated and described structures. Therefore, the present invention is not limited to the illustrated and described structures, and its scope shall be limited only by the attached claims and their equivalents.

Claims

1. An adhesive layer for a flexible image display device, which is formed from an adhesive composition containing a (meth)acrylic polymer obtained by solution polymerization, in, The (meth)acrylic polymer contains, as a monomer unit, at least one (meth)acrylic monomer having an alkyl group selected from the group consisting of n-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, and n-tetradecyl (meth)acrylate, The weight average molecular weight (Mw) of the (meth)acrylic polymer is 1.2 million to 2.5 million. The adhesive composition contains a crosslinking agent, and the crosslinking agent is at least one selected from an organic crosslinking agent and a multifunctional metal chelate. The organic crosslinking agent includes an isocyanate crosslinking agent, a peroxide crosslinking agent, an epoxy crosslinking agent, and an imine crosslinking agent. The adhesive layer is formed by drying and removing the polymerization solvent contained in the adhesive composition. The adhesive layer has a glass transition temperature (Tg) of -50°C or higher and 0°C or lower. 2 . The pressure-sensitive adhesive layer for a flexible image display device according to claim 1 , which has a storage modulus G′ at 25° C. of 1.0 MPa or less. 3 . The adhesive layer for a flexible image display device according to claim 1 , wherein the adhesive force to the polarizing plate is 5 to 40 N / 25 mm.

4. The adhesive layer for a flexible image display device according to claim 1, in, The adhesive layer has a glass transition temperature (Tg) of -45°C or higher and 0°C or lower.

5. The adhesive layer for a flexible image display device according to claim 1, in, The cross-linking agent is a combination of an isocyanate cross-linking agent and a peroxide cross-linking agent.

6. The adhesive layer for a flexible image display device according to claim 5, in, The isocyanate crosslinking agent is a trifunctional isocyanate crosslinking agent.

7. The adhesive layer for a flexible image display device according to claim 1, in, The (meth)acrylic polymer contains as a monomer unit any one of a hydroxyl group-containing monomer, a carboxyl group-containing monomer, an amino group-containing monomer and an amide group-containing monomer having a reactive functional group, and The amide group-containing monomer is any one of an N-acryloyl heterocyclic monomer and an N-vinyl-containing lactam monomer. The N-acryloyl heterocyclic monomer includes N-(methyl)acryloyl morpholine, N-(methyl)acryloyl piperidine, and N-(methyl)acryloyl pyrrolidine. The N-vinyl-containing lactam monomer includes N-vinyl pyrrolidone and N-vinyl-ε-caprolactam.

8. The adhesive layer for a flexible image display device according to claim 7, in, In the (meth)acrylic polymer, the ratio of the monomer unit of the monomer having a reactive functional group is 0.01 to 5% by weight.

9. The adhesive layer for a flexible image display device according to claim 1, in, The adhesive composition may or may not contain additives, The additive is any additive selected from the group consisting of silane coupling agent, polyether compound, colorant, powder, dye, surfactant, plasticizer, tackifier, surface lubricant, leveling agent, softener, antioxidant, anti-aging agent, light stabilizer, ultraviolet absorber, inhibitor, antistatic agent, inorganic or organic filler, and metal powder. 10 . A laminate for a flexible image display device, comprising the pressure-sensitive adhesive layer for a flexible image display device according to claim 1 , a protective film of a transparent resin material, and a polarizing film in this order.

11. A flexible image display device comprising the laminate for a flexible image display device according to claim 10 and an organic EL display panel, in, The laminate for a flexible image display device is arranged on a visible side of the organic EL display panel.